Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Pembelian Produk dan Jasa - Hasrun Afandi UmpuSinga; Chabi Baturohmah; Herma Artika Putri; Resa Salsabila (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This research is a literature review study aimed at identifying and analyzing the factors influencing consumer decisions in purchasing products and services, based on the results of previous studies. This study was compiled based on a review of fifteen national scientific journals discussing consumer decisions in various sectoral contexts, such as food and beverages, cosmetics, coffee, organic rice, mineral water, perfume, and online-based services. The results of the study indicate that consumer decisions are influenced by two main groups of factors: internal and external factors. Internal factors include motivation, perception, attitudes, lifestyle, and personality, while external factors include product quality, price, promotion, location, service, as well as social and cultural influences. Several studies also confirmed that trust, religious values, and customer satisfaction play an important role in the purchasing decision-making process, especially for products related to moral or spiritual values. By understanding these various determinants, business practitioners can design more effective marketing strategies, oriented toward consumer needs and preferences.